Identifying medical call centre stress: an evaluation of psychological and physical wellbeing - Lutrin, Josie (My University, 2006)
The current research focuses on stress within the medical call centre environment and the way in which organisational factors may impact on the psychological and physical well being of employees in such a context. The rationale of the study occurs as a relative lack of current research in this area, particulary within the South African context. Furthermore, the study aimed to combine previous research conducted in call centres with other studies carried out on emergency medical service personnel, in order to generate distinctive findings for the unique environment of the emergency medical call centre. The study was quantitative in nature and was based on the transactional model of stress. The participants were selected non-randomly from an accessible of convenience and elements of both purposive and convenience sampling procedures were used. One hundred and fifty questionnaires were distributed within the three medical call centres and 78 were completed and returned. The findings indicate that medical call employees experience stress from environmental aspects such as support from outside of work, organisational factors, feelings of being undervalued, support at work and the nature of the work itself. Additionally, findings indicated that the stress factors of support outside of work, organisational characteristics, being undervalued and support at work had and impact on the psychological and physical wellbeing of employees and increased absenteeism and their desire to leave the organisation. Results also indicated that the stress related to the nature of the work itself was not significant and decreased as tenure within the medical call centre increased. Having identified aspects of medical call centre stress and the way in which these factors impact on the psychological and physical wellbeing of employees, the implications this work were discussed both theoretically and practically. Limitations of the study were acknowledged and further research directions were suggested.
Student Number : 9901985W - MA research report - School of Psychology - Faculty of Humanities
Keywords: call centre; stress; wellbeing